An even pattern of xylan substitution is critical for interaction with cellulose in plant cell walls. (November 2017) - Grantham, Nicholas; Wurman-Rodrich, Joel; Terrett, Oliver; Lyczakowski, Jan; Stott, Katherine; Iuga, Dinu; Simmons, Thomas; Durand-Tardif, Mylene; Brown, Steven.; Dupree, Ray; Busse-Wicher, Marta; Dupree, Paul
Abstract Xylan and cellulose are abundant polysaccharides in vascular plants and essential for secondary cell wall strength. Acetate or glucuronic acid decorations are exclusively found on even-numbered residues in most of the glucuronoxylan polymer. It has been proposed that this even-specific positioning of the decorations might permit docking of xylan onto the hydrophilic face of a cellulose microfibril1–3 . Consequently, xylan adopts a flattened ribbon-like twofold screw conformation when bound to cellulose in the cell wall4 . Here we show that ESKIMO1/XOAT1/TBL29, a xylan-specificO -acetyltransferase, is necessary for generation of the even pattern of acetyl esters on xylan inArabidopsis . The reduced acetylation in theesk1 mutant deregulates the position-specific activity of the xylan glucuronosyltransferase GUX1, and so the even pattern of glucuronic acid on the xylan is lost. Solid-state NMR of intact cell walls shows that, without the even-patterned xylan decorations, xylan does not interact normally with cellulose fibrils. We conclude that the even pattern of xylan substitutions seen across vascular plants enables the interaction of xylan with hydrophilic faces of cellulose fibrils, and is essential for development of normal plant secondary cell walls. Plant cell wall consists of multiple components and complex structure. Here, ssNMR was used to investigate the physical interactions between two principle cell wall components, cellulose and xylan, and demonstrate the mechanism for their interactions